Oxygen compared to air during exercise training in COPD with exercise-induced desaturation. Issue 5 (30th May 2019) - Alison, Jennifer A.; McKeough, Zoe J.; Leung, Regina W.M.; Holland, Anne E.; Hill, Kylie; Morris, Norman R.; Jenkins, Sue; Spencer, Lissa M.; Hill, Catherine J.; Lee, Annemarie L.; Seale, Helen; Cecins, Nola; et al.
Almost half the patients referred to pulmonary rehabilitation with chronic obstructive pulmonary disease (COPD) desaturate during exercise. Although oxygen supplementation may ameliorate oxygen desaturation, the effects on outcomes of exercise training have not been rigorously evaluated. This study aimed to determine whether supplemental oxygen during exercise training was more effective than medical air in improving exercise capacity and health-related quality of life (HRQoL) in people with COPD. People with COPD who demonstrated oxygen desaturation <90% during the 6-min walk test were recruited to this multicentre trial with randomisation (independent, concealed allocation) to either an Oxygen group or Air group, blinding (participants, exercise trainers and European Respiratory Journal assessors) and intention-to-treat analysis. Both groups received the respective gas from concentrators via nasal prongs at 5 L·min −1 during exercise training consisting of treadmill and cycle exercise, three times per week for 8 weeks. Primary outcomes were the endurance shuttle walk test (ESWT) time and Chronic Respiratory Disease Questionnaire (CRQ)-Total score. 111 participants (60 males), mean±sd age 69±7 years, with moderate to severe COPD were recruited and 97 completed (Oxygen group n=52; Air group n=45). At the end of the 8-week training programme there were no between-group differences in change in ESWT (mean difference 15 s (95% CI −106–136 s) or change in CRQ-Total (0.0 points (95% CI −0.3–0.3 points)). Within-group changes at end-training were significant for ESWT and CRQ-Total (all p<0.01). Exercise capacity and HRQoL improved in both groups, with no greater benefit from training with supplemental oxygen than medical air. Exercise training improved exercise capacity and quality of life in normoxaemic COPD patients who demonstrated oxygen desaturation during exercise, with no greater improvement with supplemental oxygen during exercise training compared to air http://ow.ly/7hRP30o3vxu